2010
DOI: 10.1007/s10517-010-0971-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cytomorphological Studies of the Reaction of Mononuclear Phagocyte System in Granulomatosis of Mixed (Silicotic and Tuberculous) Etiology

Abstract: Silicon dioxide in combination with Mycobacterium tuberculosis in BCG vaccine is characterized by a significantly higher granuloma-inducing activity than BCG or silicon dioxide alone. Cell "dissociation" from granulomas is not characteristic of granulomas induced by silicon dioxide or its combination with BCG (in contrast to BCG-induced granulomas). A steady increase in the counts and size, particularly on days 120-180, mainly at the expense of fibroblast accumulation and subtotal fibrosis, are intrinsic to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…The tuberculosis loading in rats was consistent with the progress of silicosis. Interestingly, an in vitro study by Shkurupy et al 13,14 demonstrated that preliminary loading of macrophages with silicium dioxide reduced their antibacterial activity, implying that the cytotoxicity of silica dust to macrophage was the main reason for the damage to the anti-tuberculosis function. However, little was known about the detail injury mechanism and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The tuberculosis loading in rats was consistent with the progress of silicosis. Interestingly, an in vitro study by Shkurupy et al 13,14 demonstrated that preliminary loading of macrophages with silicium dioxide reduced their antibacterial activity, implying that the cytotoxicity of silica dust to macrophage was the main reason for the damage to the anti-tuberculosis function. However, little was known about the detail injury mechanism and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Так, ранее нами было показано, что про-цессы фиброзирования начинают формироваться задолго до развития процессов деструкции как в структурах, которые не принято относить к орга-нам и тканям (туберкулезные гранулемы), так и в паренхиме органов [11][12][13]. На модели генерали-зованного БЦЖ-гранулематоза у мышей призна-ки фиброзирования органов обнаруживали уже на 3-и сут после инфицирования.…”
Section: резюмеunclassified
“…Inflammatory granulomatous diseases are characterized by a high concentration of granulomas in tissue interstitium in which phagocytic cells producing reactive oxy-gen and nitrogen species (RONS) are accumulated [1][2][3]. Because of their high reactivity, free radicals react with unsaturated fatty acids that are components of membrane phospholipids, activate lipid peroxidation processes (LPP), the products of which have a cytotoxic effect [1].…”
Section: Introductionmentioning
confidence: 99%